The Effectiveness of Using the Kahoot Application for PAI Learning Evaluation of Faith in Rosul Material - Vivi Dayu Aulia; Anita Puji Astutik (At-Tarbiyat, 2023)
In the field of education, the quality of learning and teaching must be improved in accordance with the times, especially in technological developments. This aims to make students more active in learning. There are many learning evaluation media that can be used, one of which is Kahoot. This study aims to determine the Effectiveness of Using Kahoot Application for PAI Learning Evaluation of Iman Ke Rosul Material at SMKN 1 Gempol. This study uses a quantitative approach with a pretest-posttest design experimental method. In this study, the population was class XI majoring in Computer and Network Engineering (TKJ) at SMKN 1 Gempol. The sample in this study consisted of 2 classes, namely TKJ 1 and TKJ 2. Where the TKJ 1 group was used as an experimental class with the treatment given, namely using Kahoot. While the TKJ 2 group is used as a control class. From the results of data analysis using the t test, it shows that the Sig. (2-tailed) of 0.000 < 0.05, which means that the use of Kahoot is proven effective for evaluating PAI learning on Iman Ke Rosul material.